مفهوم المقاومة في الشعر العربي من منظور التطوّر التاريخي - ناصر بشير; مروشية محمد; فاضل ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The concept of resistance aesthetically is reflected in its connotative expansion and structural relations in establishing a dear and honorable homeland. This will lead us that resistance concept is not only confined to guns and arms, but rather it focuses on the core of connotation and its way to have the aesthetical counterpart that one is taken to the fact that resistance is a culture; and it is a conduct practically made not a meaningless point of view. Resistance has a numerous aspect an is distinguished from other concepts as being crystalized in the belief in nation and in confidence to eradicate injustice beside switching between rebellion and seeking for freedom for man and homeland. To be aware of reality requires to go back to the past; to have something new requires to build on what others founded and to keep abreast of their contribution in regard to have each thing deeply- rooted. So, resistance in concession of generations is always against regression, occupation and domination, namely, each matter that digests rights and estranges the same from its owner to a foreign one. Based on that, to employ the arts in resistance is not something new, and this is clearly found in literary works as per time and place. So, that we can find arts and sorts of employing literature in the service of resistance and innovation are just an expression of how resistance is so important in seeking to have a better future in order to dignity for man and his homeland إن مفهوم المقاومة، جماليّاً، يتجلى باتساعه الدلالي، وتعالقاته البنيويّة في رسم وطن كريم عزيز ، وهذا يقودنا إلى أنّ مفهوم المقاومة ليس حكراً على البندقيّة و السلاح ، بل يتركّز جوهر الدّلالة وفضاؤها في المعادل الجمالي الذي يأخذ مريده إلى حقيقة أنّ المقاومة ثقافة ، والثّقافة سلوك عملي وليست مجرّد تنظيرٍ كلامي فارغ من محتواه . وللمقاومة أشكال متعدّدة ، وميزات تميزها من غيرها من المفاهيم ؛ إذ تتبلور في الإيمان بالشعب ، والثقة بقدرته على اجتثاث الظّلم ، بالإضافة إلى تلوّنها بين التمرّد ، وطلب الحرّيّة للوطن والإنسان . إنّ وعي الواقع و تفهّمه يتطلّبان العودة إلى الماضي ، كما أنّ الحاجة إلى الجديد تستلزم التأسيس على ما انتهى إليه الأسبقون ، و مواظبة عطاءاتهم من حيث يكون لكلّ أمر أصيل جذور أصيلة . فالمقاومة في تعاقب الأجيال لا تلين عن رفض الظلم و الاحتلال والهيمنة والتسلّط ، أو بكلمة واحدة كلّ ما يسلب الحقوق ويغرّبها من مستحقّها إلى معتدٍ غريب. وعليه ، فإن توظيف الفن للمقاومة ليس جديداً ، ويظهر ذلك في تتبّعنا للآثار الأدبية عبر الزمان والمكان؛ إذ نجد صنوفاً وفنوناً من توظيف الأدب للمقاومة. وما الفوارق بين المقاومة والتجديد إلا تعبير عن أهمية المقاومة في السعي الدائم نحو واقع أفضل يحفظ كرامة الإنسان ووطنه .